Risk Factors Correlated with Incidence of Low Birth Weight Cases - Anjas Dwi Purwanto; Chatarina Umbul Wahyuni (Jurnal Berkala Epidemiologi, 2016)
One risk factor that contributes high to infant mortality especially in early and advanced neonatal periods is Low Birth Weight (LBW). About 17% of births from 25 million deliveries per year in the world are babies with LBW. LBW is caused by multifactorial factors such as maternal factors (age, level of education, maternal work status, pregnancy gap, history of illness, gestational age, parity, twin pregnancy, hypertension, anemia, behavior), placental factors, fetal factors, and environmental factors. This study aims to analyze the relationship between gestational age, twin pregnancy, hypertension, and anemia with the incidence of LBW. This research is observational research using a case-control design. The total number of samples used was 120 mothers who gave birth at Mother and Child Hospital of Kendangsari Surabaya. Subject selection uses a systematic random method. The independent variables in this study were maternal age, level of education, pregnancy gap, parity, gestational age, twin pregnancy, hypertension, and maternal anemia, while the dependent variable in this study was LBW. Based on the Chi-square statistical test results, it was found that there was a significant relationship between gestational age (p = 0,000; OR = 13,571; 95% Cl = 3,814–48,295), twin pregnancy (p = 0,001; OR = 2,224; 95% CI= 1,807-2,0738), hypertension (p = 0.037; OR = 2,753; 95% Cl = 1,040-7,292) and anemia during pregnancy (p = 0,000; OR = 4,030; 95% Cl = 1,881–8,635) with LBW events. The conclusion of this study is that there are 4 factors associated with LBW events, namely gestational age, multiple pregnancy, hypertension, and anemia during pregnancy.